A Comparison Between Inter-Asterisk eXchange Protocol and Jingle Protocol: Session Time - Haj Aliwi, H. S.; Alajmi, N. K. A.; Sumari, P.; Alieyan, K. (Engineering, Technology & Applied Science Research, 2016)
Over the last few years, many multimedia conferencing and Voice over Internet Protocol (VoIP) applications have been developed due to the use of signaling protocols in providing video, audio and text chatting services between at least two participants. This paper compares between two widely common signaling protocols: InterAsterisk eXchange Protocol (IAX) and the extension of the eXtensible Messaging and Presence Protocol (Jingle) in terms of delay time during call setup, call teardown, and media sessions.